Pemberdayaan Masyarakat Melalui TOGA untuk Pencegahan Diabetes Mellitus - Nurul Hidayah; Widya Puspitasari; Rifaatul Laila Mahmudah; Nurwidji (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2026)
Diabetes Mellitus, a non-communicable disease with an increasing prevalence, requires community-based prevention efforts through promotive and preventive approaches. The use of Family Medicinal Plants (TOGA) has been an alternative that is easy, affordable, and applicable in supporting the prevention of Diabetes Mellitus at the household level. The aim of this community service activity was to empower the community in utilizing TOGA as a preventive measure for Diabetes Mellitus and to raise awareness about the importance of simple health checks. The methods used included health counseling, TOGA planting and maintenance practices, as well as vital sign checks for early detection of disease risks. The activity was carried out on August 10, 2025, in RW 5, Sumberporong Village, Lawang District, Malang Regency, with 34 participants from the PKK group. The results showed a 50.5% increase in knowledge, positive attitudes, and skills among participants in utilizing TOGA, along with heightened awareness of the importance of monitoring health through vital sign checks. Additionally, a TOGA demonstration garden was established as an educational tool and for program sustainability. This activity had a positive impact on encouraging community independence in preventing Diabetes Mellitus. Ongoing mentoring and the development of similar programs in other areas are recommended to strengthen community-based promotive and preventive measures for non-communicable diseases.